Hepatic Hydrothorax: How Would You Manage It? - Hassan Al-sharif; Sat Sharma (Canadian Respiratory Journal)
A 53-year-old woman with a history of chronic alcoholism presented with symptomatic large right-sided pleural effusion with no evidence of ascites. After a diagnosis of hepatic hydrothorax was established, her symptoms improved with therapeutic thoracente